“Parem as máquinas! Agora é o SPAECE”: uma etnografia entre a gestão e o ensino no contexto de avaliações em larga escala em uma escola pública do interior do Ceará - Celedônio, Danilo Barroso (2023)
This thesis presents an ethnographic study centered on the process of applying large-scale assessments in a public school in the interior of Ceará, with emphasis on the test of the Permanent System of Evaluation of Basic Education of Ceará (SPAECE), of the National System of Evaluation of Basic Education in Brazil (SAEB) and the National High School Examination (Enem). As an ethnography that it is, we sought to apprehend and interpret the meanings that these assessments awaken in subjects who belong to the school – workers or students. For that, a bibliographic review, statistical surveys and, above all, field research with systematic participant observation were carried out in a public school in the interior of the state of Ceará. One of the main assumptions of the thesis is the understanding that large-scale assessments allow dialogues, sometimes tense, between two social fields, in Bourdieu's perspective (1989): that of Managerial Public Administration and that of School Education. We work here on the idea that the aforementioned fields intersect and that the subjects who experience this (re)signify public policies, in the specific case, institutional evaluation, which ends up having an impact on the type of institution that the school becomes. transforms when in contact with the instruments of managerial management. Regarding the school field, theoretical approaches were sought, in addition to Bourdieu (2016; 2018), with Beserra and Lavergne (2018), Gellner (2000), Durham (2010), among others. Regarding the field of Management, especially that of large-scale evaluation, studies by Bresser Pereira (2006), Gaulejac (2007), Balandier (2015), Haroche (2015), Cavalcanti (2007) were used. As references for anthropological analysis of public policy evaluation, Gussi (2014), Gussi and Oliveira (2016) and Rodrigues (2016) were used. The results show that the type of preparation carried out for the large-scale assessments reinforces improvisation as an administrative resource, as well as the memorization of contents as a teaching practice, in addition to causing discomfort in some professionals due to the readjustment of time and the priorities agreed in the annual plans. Thinking about school assessments, especially at times of tests, as rituals (PEIRANO, 2002; TURNER, 2013; MCLAREN, 1991), it is clear that they cross these liminal moments so dear to the school community and provoke resignifications of work and weights of the learnings. Another finding of this ethnographic research is the perception that the symbolic hierarchy between school management and teaching provoke, in these resignifications of school work, a series of resentments among professionals, something that also extends to students, especially when their priorities are relegated to second plan.